2015 International Conference on Interactive Collaborative Learning (ICL) 2015
DOI: 10.1109/icl.2015.7318197
|View full text |Cite
|
Sign up to set email alerts
|

Mobile technologies in engineering education

Abstract: Mobile devices are emerging technologies that are being integrated into Engineering Education. They not only allow learning anytime and anywhere but also use everyday-life resources in the teaching-learning process. Education based on mobile devices is called mobilelearning or m-learning. This paper proposes a set of mlearning practices for subjects of the curricular areas (Basic Sciences, Basic Technologies, Applied Technologies and Complementary Training) included in engineering degree programmes. Such pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The module is developed to be operated in a mobile device, which requires a specified requirement to optimally utilize the module [14]. For that purpose, a series of test was performed to determine the ability of a software with a certain memory capacity in running all functions of mobile-based application module on the smartphone.…”
Section: Resultsmentioning
confidence: 99%
“…The module is developed to be operated in a mobile device, which requires a specified requirement to optimally utilize the module [14]. For that purpose, a series of test was performed to determine the ability of a software with a certain memory capacity in running all functions of mobile-based application module on the smartphone.…”
Section: Resultsmentioning
confidence: 99%
“…Mobile learning is certainly not merely the conjunction of 'mobile' and 'learning'; it has always implicitly meant 'mobile e-leaning' and its history and development have to be understood as both a continuation of 'conventional' E-learning and reaction to this 'conventional' e-learning and to its perceived inadequancies and limitation [11]. M-learning is a relatively new trend in the development of e-learning with the help ofdevice a mobile so that users have access to the learning materials anywhere, anytime [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research on mobile learning has been widely carried out, such as mobile technologies in engineering education [11], the mobile learning for education: benefits and Challenges [12], Defining mobile learning in the higher education landscape [13]. Some of these studies only examine the problems of implementing mobile learning in higher education and technical education, no studies have investigated the potential use of mobile learning in vocational secondary school level.…”
Section: Introductionmentioning
confidence: 99%
“…They were classified into two groups: 82.8% developed applications using ETs. For example Kevan and Ryan [29] used the emerging technology (ET) API to generate applications for learning, Herrera et al, [30] designed mobile applications to improve generic competencies and Navarro et al [31] developed serious games using open-source tools and 17.2% of the studies not only developed the application but also implemented and evaluated it (e.g., [32]). 20 studies were found in models, approaches, methodologies or frameworks.…”
Section: Type Of Documentmentioning
confidence: 99%